2010
DOI: 10.1111/j.1745-4603.2010.00252.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving Textural Characteristics of Tortillas by Adding Gums During Extrusion to Obtain Nixtamalized Corn Flour

Abstract: Whole white corn was ground, and lime, water and xanthan gum (XG, 0.5% w/w), carboxymethylcellulose (CMC, 0.5% w/w), guar gum (GG, 0.5% w/w) or a gums mix (XG, 0.25% w/w; CMC, 0.15% w/w; GG, 0.10% w/w) were added. Blends were extruded, dried and ground to obtain nixtamalized corn flour (ENCF), and they were used to make tortillas. The particle size distribution, particle size index, water absorption capacity (WAC) and water absorption index (WAI) were determined in flour; moisture content and viscoelastic char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(68 citation statements)
references
References 25 publications
(75 reference statements)
6
61
1
Order By: Relevance
“…Dynamic rheology has measured efficiently the viscoelastic properties of materials, especially starch [57]. Sahai et al [34] found a strong relationship between textural attributes of masa obtained from TPA, the particle size, and the composition.…”
Section: Texture and Rheology Of Nixtamalized Productsmentioning
confidence: 99%
See 4 more Smart Citations
“…Dynamic rheology has measured efficiently the viscoelastic properties of materials, especially starch [57]. Sahai et al [34] found a strong relationship between textural attributes of masa obtained from TPA, the particle size, and the composition.…”
Section: Texture and Rheology Of Nixtamalized Productsmentioning
confidence: 99%
“…Using other concentrations, the viscosity decreased. The viscosity in ENCF is also increased during the production process with the addition of gums [3,57] and enzymes [68]. The effect of alkaline cooking and lime concentration (from 0 to 1.0%) had direct impact on the viscosity of corn masa, when a Brabender amylograph was used to measure viscosity [6].…”
Section: The Increase Of the Soluble Fiber Content (Expressed As Dmentioning
confidence: 99%
See 3 more Smart Citations